The Role Of Interfaith Dialogue In Enhancing Global Peacebuilding - Sahri; Himad Ali (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
In an increasingly interconnected and multicultural world, religious diversity has become both an asset and a challenge for global peacebuilding. Interfaith dialogue emerges as a pivotal tool for fostering mutual understanding, reducing religious tensions, and promoting social cohesion. This study adopts a qualitative comparative approach to examine interfaith dialogue initiatives in Southeast Asia and Europe, focusing on their strategies, challenges, and outcomes. In Southeast Asia, countries like Indonesia, Malaysia, and Thailand employ grassroots, community-driven approaches through platforms such as the Forum Kerukunan Umat Beragama (FKUB), Harmony Week, and Buddhist-Muslim peace projects, emphasizing cultural sensitivity and local engagement. Conversely, Europe, represented by Germany, France, and the United Kingdom, relies on institutional and policy-driven frameworks such as the German Conference on Islam, the French Conseil Français du Culte Musulman (CFCM), and the UK Inter Faith Network to manage religious pluralism and integration. The comparative findings reveal that while Southeast Asia excels in bottom-up, culturally embedded practices, Europe demonstrates the effectiveness of top-down, structured frameworks supported by government policies. Integrating these approaches offers a hybrid model for enhancing global peacebuilding. The study concludes that fostering interfaith collaboration and knowledge exchange is essential for addressing religious conflicts and achieving sustainable global harmony.